2013
DOI: 10.1159/000345298
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Epicardial Fat Thickness and Cardio-Ankle Vascular Index to Complexity of Coronary Artery Disease in Nondiabetic Patients

Abstract: Objectives: Arterial stiffness and epicardial fat thickness (EFT) are associated with coronary artery disease (CAD). The cardio-ankle vascular index (CAVI) is a novel marker of arterial stiffness. The SYNTAX score (SS) reflects the complexity of CAD. We aimed to evaluate the relation of EFT and CAVI with CAD complexity in nondiabetic patients. Method: We enrolled 121 patients undergoing coronary angiography. In all patients, CAVI and EFT were determined. SS were calculated. The relationship between EFT, CAVI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
1
20
0
6
Order By: Relevance
“…Furthermore, in contrary to other methods of arterial stiffness measurements including pulse wave velocity, augmentation index and aortic elastic properties, CAVI is not a regional stiffness parameter instead reflects the stiffness of whole arterial tree. Recent studies have shown that CAVI is correlated with subclinical parameters of atherosclerosis including carotid intima media thickness and epicardial fat thickness (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in contrary to other methods of arterial stiffness measurements including pulse wave velocity, augmentation index and aortic elastic properties, CAVI is not a regional stiffness parameter instead reflects the stiffness of whole arterial tree. Recent studies have shown that CAVI is correlated with subclinical parameters of atherosclerosis including carotid intima media thickness and epicardial fat thickness (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…In opposed to Saji et al (30) we studied the patients that underwent coronary angiography and intervention due to acute coronary syndrome and we found that, the cut-off value of CAVI for the development of SNI was 10.45 (sensitivity=71.8%, specificity=91.5%) in ROC analysis. CAVI is increased in patients with established CAD therefore the higher cut-off value that is detected in our study may be due to the concomitant presence of CAD (31).…”
Section: Discussionmentioning
confidence: 47%
“…Так, у больных сахарным диабетом 2-го типа СЛСИ позитивно коррелировал с кальциевым индек-сом коронарных артерий, определяемым при мульти-спиральной компьютерной томографии (r=0,303, p<0,0001) [10]. Также есть свидетельства о наличии связи между СЛСИ и распространенностью [11] и выраженностью коронарного атеросклероза [6,9,12,13]. Так, при отсутствии стенозов КА СЛСИ составил 8,34±1,01, при стенозах одной, двух и трех КА -8,44±1,39; 9,95±1,22 и 10,12±1,56, соответственно, (р<0,05) [9].…”
Section: Discussionunclassified
“…В недавней работе отмечена положительная корреляционная связь между СЛСИ и выраженностью поражения коронарных артерий по шкале SYNTAX (r=0,537; p<0,001). Значения СЛСИ 8,6 и выше были предиктором средней степени или тяжелого пораже-ния КА по шкале SYNTAX (площадь под кривой -0,877, 95% ДИ 0,805-0,929) со специфичностью 68,9% и чувствительностью 93,5% [6].…”
Section: Discussionunclassified
See 1 more Smart Citation